952 When A Surgeon Was Called to The Obstetric Unit: A Rare Case of Gonococcal Peritonitis in A 12-Week Pregnancy. (12th October 2021) - Ann Jacob, P; Jacob, L
Abstract: Background: Primary bacterial peritonitis presenting as septic shock is infrequently seen in clinical practice. This is a case of gonococcal peritonitis presenting as septic shock in a pregnant lady needing emergency laparotomy, drainage of purulent fluid and abdominal lavage. Case Presentation: A 35-year-old woman presented with severe generalised abdominal pain. No history of fever, vomiting, urinary or bowel complaints. She was in her 4 th pregnancy, at 12-weeks gestation. She was afebrile but tachycardic and hypotensive. Abdomen was tender and there was no vaginal bleeding. Ultrasound scan showed minimal fluid in hepatorenal area and a viable intrauterine pregnancy. Differential diagnosis were ruptured appendix, ectopic pregnancy, acute abdomen and shock. Exploratory laparotomy was done. Moderate amount of purulent fluid was noted within the abdominal cavity and no bleeding was seen. General surgeon was called for assistance by the Obstetrician as no foci of infection was found. The uterus, fallopian tubes, ovaries, appendix, bowel and upper abdominal organs were found to be intact. Peritoneal fluid culture was taken. Drainage of purulent fluid and peritoneal wash was done. She was nursed in ICU because of peritonitis with septic shock and AKI. Peritoneal fluid culture showed Neisseria gonorrhoea and IV ceftriaxone was given for 7 days. Postoperatively she recovered well but needed evacuation of uterus for a missed miscarriage. She was screened for other STIs and were negative. Discussion: Gonorrhoea is the second most common reported STI. It can present as acute peritonitis when the infection has spread beyond upper reproductive tract organs.